La naturaleza del procedimiento de selección de contratistas y el carácter común de la Ley del Procedimiento Administrativo General - Shimabukuro Tokashiki, Néstor (2018)
The special nature of the contractor selection procedure and the source hierarchy of the State Procurement Law have been used as an argument to support the non-application of the interoperability rule within the framework of these procedures. Being in disagreement with this position, we sustain in the article that the special nature of the selection procedure does not negate the application of the informalism principle that underpins the interoperability rule. Likewise, we maintain that the common character of the Law of General Administrative Procedure, where the principle of informalism is enshrined, requires a reinterpretation of the hierarchy of sources of the State Contracting Law.